Nature of defects in blue light emitting CaZrO3: spectroscopic and theoretical study. Issue 70 (31st July 2015) - Gupta, Santosh K.; Ghosh, P. S.; Pathak, N.; Tewari, R.
<x xml:space="preserve">Abstract</x> Defects responsible for intense blue emission in CaZrO3 are investigated using PL and EPR spectroscopy and complimented by DFT calculations.